2017
DOI: 10.1111/tri.13002
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus and mycophenolate regimen and subclinical tubulo-interstitial inflammation in low immunological risk renal transplants

Abstract: The aim was to evaluate the relationship between maintenance immunosuppression, subclinical tubulo-interstitial inflammation and interstitial fibrosis/tubular atrophy (IF/TA) in surveillance biopsies performed in low immunological risk renal transplants at two transplant centers. The Barcelona cohort consisted of 109 early and 66 late biopsies in patients receiving high tacrolimus (TAC-C target at 1-year 6-10 ng/ml) and reduced MMF dose (500 mg bid at 1-year). The Oslo cohort consisted of 262 early and 237 lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(33 reference statements)
1
9
1
Order By: Relevance
“…This difference from our study may be attributable to their conversion from tacrolimus to sirolimus and a lower maintenance MMF dose in patients with NOMOA. 2830 Finally, the steroid-based arm (n = 70) of the multicenter SNS01-NIH-CCTPT study found a 35% lower rate of subclinical inflammation in 6-month surveillance biopsies, but was also less racially diverse than our study. 26 Our data from a diverse pediatric cohort provide a significant addition to the existing literature on outcomes after surveillance biopsies.…”
Section: Discussioncontrasting
confidence: 50%
“…This difference from our study may be attributable to their conversion from tacrolimus to sirolimus and a lower maintenance MMF dose in patients with NOMOA. 2830 Finally, the steroid-based arm (n = 70) of the multicenter SNS01-NIH-CCTPT study found a 35% lower rate of subclinical inflammation in 6-month surveillance biopsies, but was also less racially diverse than our study. 26 Our data from a diverse pediatric cohort provide a significant addition to the existing literature on outcomes after surveillance biopsies.…”
Section: Discussioncontrasting
confidence: 50%
“…140-145 In contrast, while some studies have linked the use of mycophenolate to reduced dnDSA formation, 146,147 the impact of MPA dose or exposure on dnDSA formation is largely absent. Torres et al 141 linked tubulointerstitial inflammation in low-risk recipients with combination of low tacrolimus concentrations and reduced MMF dosing, while Filler et al 148 reported a significant association between minimum MPA trough concentrations and dnDSA formation in pediatric renal transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Since tacrolimus and mycophenolate were introduced, the prevalence of tubulointerstitial inflammation in the first 2 years (subclinical aTCMR and borderline changes) has fallen from >50% to ∼10% of transplant recipients ( 71 ). In addition, severity of inflammation has decreased to the point that subclinical aTCMR in protocol biopsies constitutes an uncommon diagnosis ( 63 ).…”
Section: Incomplete Inflammatory Phenotypesmentioning
confidence: 99%